Opposite Antipodal Fundamental Solution of Laplace's Equation in Hyperspherical Geometry - Cohl, H.S. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
Due to the isotropy of d-dimensional hyperspherical space, one expects there to exist a spherically symmetric opposite antipodal fundamental solution for its corresponding Laplace-Beltrami operator. The R-radius hypersphere SdR with R>0, represents a Riemannian manifold with positive-constant sectional curvature. We obtain a spherically symmetric opposite antipodal fundamental solution of Laplace's equation on this manifold in terms of its geodesic radius. We give several matching expressions for this fundamental solution including a definite integral over reciprocal powers of the trigonometric sine, finite summation expressions over trigonometric functions, Gauss hypergeometric functions, and in terms of the Ferrers function of the second with degree and order given by d/2−1 and 1−d/2 respectively, with real argument x∈(−1,1).